Ending Food Poverty Through Trade: Evidence from Manufacturing Exports in South Africa (Business and Economic Analysis Journal, 2022)
As South Africa struggles to deal with many of its socio-economic challenges including poverty, this paper was interested to empirically unpack how trade specifically manufacturing exports are contributing towards poverty reduction in the country. The study was motivated by the decent increase in exports especially in the manufacturing sector over time whilst poverty levels increase. We employed time series data spanning 1990-2020 in a Vector Error Correction Model (VECM). Using the food poverty line index as the dependent variable, we found that exports from the manufacturing sector were significant in explaining food poverty reduction. Also economic growth and the human development index (HDI) were found to have poverty reducing effects in the long-run. Interestingly, we found foreign direct investment increasing food poverty in South Africa in the long-run but reducing it in the short-run. Policy recommendations arising from our results are that, South African authorities should consider pursuing more export led growth policies especially in industries that can absorb labour from those with little or no skills. Also, foreign direct investment should be encouraged in sectors that are not labour substitutive so that more inflows can lead to reduced food poverty through job creation in the long-run.